2015
DOI: 10.1016/j.corsci.2015.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of hydrogen-induced damage in friction stir welded low carbon steel joints

Abstract: Hydrogen-induced damage including blister and cracking in friction stir welded low carbon steel were evaluated by the cathodic hydrogen charging method. After hydrogen charging for 2 hours, irreversible dome-shaped blisters and internal cracking began to appear on the surface of the base metal. However, after hydrogen charging for 16 hours, cracking formed along the thermo-mechanically affected zone boundary, while the blisters or cracking were hardly observed in the stir zone. In addition, the stir zone showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The microstructural changes inside the material and mechanical properties affected by the introduced hydrogen were not illustrated. More recently, Sun et al also found -3 -the suppression of hydrogen-induced damage in the friction stir weled low carbon steel joints [21].…”
Section: Introductionmentioning
confidence: 96%
“…The microstructural changes inside the material and mechanical properties affected by the introduced hydrogen were not illustrated. More recently, Sun et al also found -3 -the suppression of hydrogen-induced damage in the friction stir weled low carbon steel joints [21].…”
Section: Introductionmentioning
confidence: 96%
“…Some microstructures are more susceptible to HE, such as coarse microstructures, 2,40,41 the interface between the ferrite and the banded mixed bainite and pearlite, by the existence of inclusions parallel and along with the bands, 34 bainite and martensite/austenite (M/A) interface, 40,41 as well as by the presence of higher dislocations volume fraction in the microstructural components of the fusion zone 42 . Few studies were dedicated to the effects of hydrogen on the mechanical properties of FSW welded joints of pipeline steels 2,14,32,43 . In the API 5L X80, high‐strength pipeline steel welded by friction‐stir welding, the stir zone (SZ) showed less ductility than the base metal (BM), indicating the improved resistance to HE of the FSW.…”
Section: Introductionmentioning
confidence: 99%
“…42 Few studies were dedicated to the effects of hydrogen on the mechanical properties of FSW welded joints of pipeline steels. 2,14,32,43 In the API 5L X80, highstrength pipeline steel welded by friction-stir welding, the stir zone (SZ) showed less ductility than the base metal (BM), indicating the improved resistance to HE of the FSW. This improved resistance was caused by the microstructure refinement in the SZ, including the ferrite matrix grain size and cementite particles.…”
Section: Introductionmentioning
confidence: 99%
“…With the resources of oil and nature gas largely exploited, those petroleum and natural gas fields that were discovered in recent years are mostly distributed in remote regions with harsh geography and climate conditions. Particularly, most petroleum and natural gas deposits are acidic and can include hydrogen sulfide gas (H 2 S), which requires pipeline steel itself having higher resistance to hydrogen‐induced cracking (HIC) and sulfide stress corrosion cracking (SSCC) . Therefore, researchers have not only continuously improved the strength, toughness, and weldability of pipeline steel but also paid more attention to corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%